Combating Identity Threat of Machine: The effect of group-affirmation on humans’ intellectual performance loss - Young-Jae Cha(차영재); Sojung Baek(백소정); Hyung-Suk Lee(이형석); Jonghoon Bae(배종훈); Jongho Lee(이종호); Sang-Hun Lee(이상훈); Gunhee Kim(김건희); Dayk Jang(장대익) (Korean Journal of Cognitive Science, 2019)
Motivation of human individuals to perform on intellectual tasks can be hampered by identity threat from intellectual machines. A laboratory experiment examined whether individuals’ performance loss on intellectual tasks appears under human identity threat. Additionally, by affirming alternative attributes of human identity, researchers checked whether group-affirmation alleviate the performance loss on intellectual tasks. This research predicted that under high social identity threat, individuals’ performance loss on the intellectual tasks would be moderated by valuing alternative attributes of human identity. Experiment shows that when social identity threat is increased, human individuals affirmed alternative human attributes show higher performance on intellectual tasks than individuals non-affirmed. This effect of human-group level affirmation on performance loss did not appear in the condition of low social identity threat. Theoretical and practical implications were discussed. KCI Citation Count: 0